Enhancing Elementary Students' Learning Interest in Science with the 'Make-a-Match' Cooperative Learning Model - Kusumaningtyas, Dian Artha; Mirtasari, Septi (International Journal of Learning Reformation in Elementary Education, 2024)
The objective of this study is to enhance students' engagement in learning natural sciences through the implementation of the 'Make-a-Match' cooperative learning model. The research was conducted with fifth-grade students at a public primary school in Purworejo, Indonesia comprising 19 students, with 14 males and 5 females. Employing a class action research design, the independent variable was the 'Make-a-Match' cooperative learning model, while the dependent variable was students' learning activity in natural sciences. Data were gathered through observation, documentation, and field notes, with analysis focused on observations of the learning process conducted by both teachers and students. Findings revealed an initial average of 48.75% in the first cycle, increasing to 75.83% in the second cycle. These results demonstrate that the application of the 'Make-a-Match' cooperative learning model effectively enhances students' learning activity in the science subject among fifth-grade elementary school students.